Allele substitution effects of IGF1, GH and PIT1 markers on estimated breeding values for weight and reproduction traits in Canchim beef cattle - Grossi, Daniela do Amaral; Grupioni, Natalia Vinhal [UNESP]; Buzanskas, Marcos Eli [UNESP]; de Paz, Claudia Cristina Paro; Regitano, Luciana Correia de Almeida; de Alencar, Maurício Mello; Schenkel, Flávio Schramm; Munari, Danísio Prado [UNESP] (Elsevier, 2015)
The aim of this study was to evaluate the allele substitution effects of IGF1, GH and PIT1 markers on the estimated breeding values (EBVs) for birth (BW) and weaning weights (WW), weight at 12 (W12) and 18 (W18) months of age, weight (WFC) and age (AFC) at first calving, and scrotal circumference measured at 12 (SC12) and 18 (SC18) months of age in Canchim beef cattle. Maternal effects were considered for birth (BWmaternal) and weaning (WWmaternal) weight. Regression analyses were carried out considering the EBVs, obtained from multi-trait analyses, and the deviations for each allele studied (four alleles for the IGF1 markers and two for GH and PIT1 markers, respectively). According to the results obtained for IGF1, the substitution effect of the 225 allele was significant (P≤0.05) and presented higher EBVs for BW, BWmaternal, WW, W12, W18, and SC18; and lower EBVs for WWmaternal. The allele substitution effect observed for GH gene was significant (P≤0.05) on EBVs for AFC and WFC. The Valine allele was responsible for lower EBVs for AFC and higher EBVs for WFC. For the PIT1 gene, the substitution effect of the Hinf- allele was significant (P≤0.05) on the EBVs for WW, WWmaternal, AFC, and WFC, respectively. Important allele substitution effects were found for weight and reproduction traits in Canchim cattle. In general, markers on the IGF1 gene are related to higher EBVs for weight, while markers on the GH and PIT1 showed greater influence on the EBVs for age and weight at first calving. Adding molecular markers information on the selection process could result in increased genetic gains in Canchim cattle. Future studies using high-density genotyping platforms may contribute to our understanding of the effects of these genes on traits of economic importance in the Canchim breed.
Keywords: Animal breeding; Association analysis; Beef cattle; Quantitative trait loci; Regression coefficient